FIGHT FOR EDUCATION: A BLACK PAPER and BLACK PAPER TWO: THE CRISIS IN EDUCATION (Editors: C. B. Cox and A. E. Dyson) - Burridge, Trevor (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1970)
C. B. Cox and A. E. Dyson, (eds.). FIGHT FOR EDUCATION: A BLACK PAPER and BLACK PAPER TWO: THE CRISIS IN EDUCATION. London: The Critical Quarterly Society, 1969, 80 pp. &. 160 pp., 5/- &. 10/-.